User experiences with second-generation 32-gauge × 4 mm vs. thinner comparator pen needles: prospective randomized trial. (2nd October 2020) - Gibney, Michael A.; Fitz-Patrick, David; Klonoff, David C.; Whooley, Shahista; Lu, Betty; Yue, Wen; Glezer, Stanislav
Abstract: Objective: Two similarly designed studies compared user experiences with a second-generation extra-thin-wall, 5-bevel 32 G × 4 mm pen needle (PN) with redesigned hub versus four thinner commercially available PNs. Methods: Adults (18–75 years old) with type 1 or type 2 diabetes and ≥3 months of experience with pen injectors qualified for single-visit, single-blinded randomized studies. The investigational 32 G PN was compared with three 33–34 G × 3.5–4 mm PNs in Study 1 and one 34 G × 4 mm PN in Study 2. Participants completed 12 abdominal injections of 0.3 mL sterile saline using insulin pens in 6 pairs, each comprising one investigational 32 G PN and one comparator PN in random order. After each injection pair, participants compared injection pain via relative 150 mm visual analog scale (VAS) and perceived dose delivery force via relative 5 point Likert scale. Adjusted models tested injection pain scores (primary endpoint) for noninferiority and, if met, then for superiority. ClinicalTrials.gov identifiers: NCT03878758 and NCT03878745. Results: The investigational 32 G PN met noninferiority as well as superiority criteria for less injection pain vs. each comparator ( p < .01), with adjusted mean relative VAS scores 9.1–17.6 in Study 1 ( n = 154) and 7.3 in Study 2 ( n = 55). The investigational 32 G PN was also superior vs. each comparator PN in requiring less relative perceived force to deliver the dose ( p < .01). Conclusions: The investigational 32 G PN was associated with less participant-reported injection pain and less perceived dose delivery force compared with four thinner PNs, suggesting no additional pain reduction or force reduction benefit conferred by the thinner PNs.